0.55–1.8 V, 7.5 nW, 225.5 mV, CMOS‐only subthreshold voltage reference. Issue 6 (1st March 2019) - Duan, Quanzhen; Wang, Xuan; Huang, Shengming; Ding, Yuemin; Meng, Zhen; Shi, Kai
Abstract : This Letter presents a wide supply voltage range, ultra‐low power, and CMOS‐only subthreshold voltage reference. A complementary‐to‐absolute‐temperature ( V CTAT ) generator implemented by a standard V TH transistor and a high V TH transistor is used to obtain a negative temperature coefficient (TC) voltage. While, a proportional‐to‐absolute‐temperature ( V PTAT ) generator adopts a unbalanced differential pair to achieve a positive TC voltage. With both V CTAT generator and V PTAT generator, the CMOS‐only voltage reference circuit is proposed, which is implemented in a standard 0.18 μ m CMOS process. The simulation results show that the mean output reference voltage is 225.5 mV at room temperature with a supply voltage as low as 0.55 V, meanwhile the output reference voltage achieves a TC of 21.9 ppm / ° C with a temperature range from − 20 to 80 ° C . With a supply voltage of 0.55 V and at room temperature, the current consumption is 13.6 nA and the power consumption is only 7.5 nW. The reference circuit correctly works with a supply voltage ranging from 0.55 to 1.8 V, and it obtains the line regulation of 0.0022%/V.